Evaluating the impact of science-enrichment programs on adolescents' science motivation and confidence: The splashdown effect - Stake, Jayne E.; Mares, Kenneth R. (Journal of research in science teaching, 2005)
The impact of summer science‐enrichment programs on high‐school students' science motivation and confidence was evaluated in a 7‐month period following program completion. The programs took place on a college campus. The splashdown effect was defined as program‐related changes the program graduates recognized in themselves that became apparent to them after reentry to their home high school. The effect was studied in a group of 88 gifted girls and boys from 38 high schools. On qualitative and quantitative measures obtained during private interviews, students reported a strong splashdown effect after returning to their high school. Results supported the validity of the splashdown concept. Splashdown motivation and splashdown confidence (i.e., recognition of program‐related gains in motivation and confidence that occurred after high‐school reentry) predicted change in corresponding science attitudes during the follow‐up period. As predicted by social comparison theory, the intensity of the splashdown effect was associated with average school achievement in the student's home high school. Students from academically weaker schools reported stronger splashdown effects. Implications for enhancing and evaluating the effect of science‐enrichment programs on students' science attitudes are discussed. © 2005 Wiley Periodicals, Inc. J Res Sci Teach 42: 359–375, 2005